Improved learning outcomes for 60 meter sprint running using traditional games in SDN Pulo Lor 1 Class VI Kabupaten Jombang. - Zakaria Wahyu Hidayat; Faisol Hamid; Aditya Harja Nenggar (Universitas Sebelas Maret, 2024)
Mastery of basic running movements is a basic element in running, especially short distance running. The benchmark for success in running training is students' mastery of basic running movements. Students in elementary schools generally do not have good skills, so this element of movement must receive priority in development. One of the important running numbers is speed. When doing basic running training, it turns out that the ability in this matter is still low. The running ability of class VI students at SD Negeri Pulo Lor 1 Jombang Regency is still low. Classroom action research was then carried out to see the improvement in learning outcomes of 49 students by providing treatment with the black and green and gobak sodor games. Conclusions of the research on the results of learning skills for running a short distance of 60 meters using traditional games for class VI students at SD Negeri Pulo Lor 1 Jombang. On average there was an increase in results starting from cycles I and II which had been given from cycles I and cycles II an increase of 34.7%. The average score shows the student's level of completeness. By implementing this traditional game, students' learning skills improve and teachers are more creative and innovative in managing learning.